Communicating Transcendent Love: Interpersonal Encounter and Church–State Transitions in Fratelli tutti - Jon P. Radwan; Roger B. Alfani (Religions, 2022)
This essay analyzes Pope Francis’ social teaching on relationality within his 2020 encyclical letter Fratelli tutti [Brothers all]. The relationship between the Church and modern nation-states is an important macro-level social dynamic, and Francis explains it by placing Church–State relations into a broader spiritual context of human communication and interaction. He articulates norms of fraternal contact growing from the bottom-up, that is, from interpersonal encounters through groups and movements on to countries and the United Nations. After a focused research question and discussion of critical method, this article offers a rhetorical critique of Fratelli tutti. To provide context, it explains the genres of Judeo-Christian and papal communication, Francis’ biography, and the immediate global context of his encyclical. Working within the text, this study details the Biblical foundations of his argument for “fraternity and social friendship” and shows how they are applied to global social media dystopia and accelerating migration/border crises. Conclusions include the utility of Francis’ contact terms in analyzing complex religio-political dynamics and their value in advancing peace.